1997
DOI: 10.1002/(sici)1097-0142(19971115)80:10<1966::aid-cncr14>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin-based versus cisplatin-based chemotherapy in the treatment of surgically incurable advanced bladder carcinoma

Abstract: M-CAVI is less toxic but less active than M-VAC in the treatment of patients with advanced bladder carcinoma. Carboplatin-based regimens in which carboplatin is administered at the dose range used in the current study should be reserved for patients who cannot tolerate cisplatin treatment. Further research is required to assess the impact of high dose carboplatin in the treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(77 citation statements)
references
References 28 publications
0
73
0
3
Order By: Relevance
“…Overall, the median and 3-year survival were 42 months (95% confidence interval [CI), 33-51) and 54% (95% CI, 48-61), respectively. Considering only those patients with high-risk features, the median and 3-year survival were 16 months (95% CI, [12][13][14][15][16][17][18][19][20] and 19% (95% CI, 5-33), respectively. For patients with or without preoperative CKD, the median survival and 3-year survival were 37 months (95% CI, 29-44) and 51% (95% CI, 42-59) and 64 months (95% CI, 34-104) and 58% (95% CI, 49-68), respectively (P ¼ .007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the median and 3-year survival were 42 months (95% confidence interval [CI), 33-51) and 54% (95% CI, 48-61), respectively. Considering only those patients with high-risk features, the median and 3-year survival were 16 months (95% CI, [12][13][14][15][16][17][18][19][20] and 19% (95% CI, 5-33), respectively. For patients with or without preoperative CKD, the median survival and 3-year survival were 37 months (95% CI, 29-44) and 51% (95% CI, 42-59) and 64 months (95% CI, 34-104) and 58% (95% CI, 49-68), respectively (P ¼ .007).…”
Section: Resultsmentioning
confidence: 99%
“…However, carboplatin-based and other noncisplatin based regimens are widely considered to be inferior to MVAC and gemcitabine-cisplatin. 12,[19][20][21] For example, in a randomized trial of MVAC versus methotrexate-vinblastine-carboplatin in patients with metastatic UC, a significantly reduced cancer-specific survival was seen in patients receiving methotrexate-vinblastine-carboplatin (median 9 vs 16 months, P ¼ .03). 19 A single-study arm phase 2 trial of neoadjuvant paclitaxel-gemcitabine-carboplatin for muscleinvasive UC of the bladder also reported fewer pathologic complete responses than had been reported in other trials of neoadjuvant CBCC in similar patients.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II trials of carboplatin, as a substitution for cisplatin in first-line chemotherapy regimens, demonstrated that carboplatin-based therapy was less effective than cisplatin-based therapy. However, there is few data on carboplatin as a substitution for cisplatinbased therapy in second-line chemotherapy (Petrioli et al, 1996;Bellmunt et al, 1997). Randomised trials with carboplatin-based regimens in patients who failed first-line platinum-based chemotherapy and development of new combinations consisting of safer and more effective agents is needed for the treatment of patients with depleted marrow reserves and impaired renal function after the failure of first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Carboplatin exhibits less nephrotoxicity and no ototoxicity and is often used as an alternative for cisplatin (7). Cisplatin has demonstrated superior activity over carboplatin in several studies of patients with squamous cell carcinoma of the head and neck (SCCHN) and bladder cancer (8)(9)(10)(11)(12). A meta-analysis of randomized trials comparing cisplatin versus carboplatin-based therapy in patients with bladder cancer demonstrated that cisplatin-based therapy significantly improved complete response and overall response compared with carboplatin (13).…”
Section: Introductionmentioning
confidence: 99%